Penerapan Model Problem Based Learning untuk Meningkatkan Hasil Belajar Pembelajaran Tematik Terpadu Kelas V - Liza, Mona; Arwin, Arwin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
This study aims to describe the learning results improved by applying a model of integrated thematic study on PBL. This research approach was qualitative and quantitative. Types of penelitianya are the PTK. Research conducted in SDN 15 Ulu Gadut kota Padang. The techniques used are observation, tests and tests. Observational research results RPP cycle I with 92.19% percentage increase in cycle II becomes 96,87%. Aspects of teacher cycle I by 87.5% percentage increase in cycle II becomes 92,85%. Aspects of the learners I cycle with 87.5% percentage increase in cycle II becomes 92,85%. On the attitude of the people there are 8 cycle and cycle II there are 8 learners had attitude stands out. Aspects of the knowledge cycle I with an average increased 75.15 cycle II with an average of 83.96. Aspects of skills on a cycle I by averaging 82.25 escalated on cycle II with an average 87.18. This proves that the PBL model can improve the learning process and student learning outcomes.